2016
DOI: 10.1002/mc.22478
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants involved in oxidative stress, base excision repair, DNA methylation, and folate metabolism pathways influence myeloid neoplasias susceptibility and prognosis

Abstract: Myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) share common features: elevated oxidative stress, DNA repair deficiency, and aberrant DNA methylation. We performed a hospital-based case-control study to evaluate the association in variants of genes involved in oxidative stress, folate metabolism, DNA repair, and DNA methylation with susceptibility and prognosis of these malignancies. To that end, 16 SNPs (one per gene: CAT, CYBA, DNMT1, DNMT3A, DNMT3B, GPX1, KEAP1, MPO, MTRR, NEIL1, NFE2F2, OGG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 119 publications
0
14
0
Order By: Relevance
“…Limitations due to sample size are common in scientific publications, as stated by Danjou et al 39 and Gonçalves et al 40. We found significant associations and correlations, but the number of cases evaluated was low and we cannot exclude the possibility that the absence of associations related to other genes might be explained by this factor.…”
Section: Discussionmentioning
confidence: 51%
“…Limitations due to sample size are common in scientific publications, as stated by Danjou et al 39 and Gonçalves et al 40. We found significant associations and correlations, but the number of cases evaluated was low and we cannot exclude the possibility that the absence of associations related to other genes might be explained by this factor.…”
Section: Discussionmentioning
confidence: 51%
“…TEC, a non-receptor type protein-tyrosine kinase, was revealed to be highly expressed in MDS patients (31). GPX1 , which encodes a glutathione peroxidase and helps to reduce organic hydroperoxides and hydrogen peroxide (H 2 O 2 ) by glutathione, has been reported to be dramatically upregulated in AML and relate with MDS by SNPs assay and DNA methylation (32,33). ASS1 (Argininosuccinate synthetase 1) gene product is responsible for the process of arginine biosynthesis; however, Miraki-Moud et al (34), reported that most AML lacked ASS1 expression, which may be due to small sample size and the different detection methods.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies associate hOGG1 Ser326Cys polymorphism with risk of other types of cancer such as hepatocellular carcinoma (HCC), [153], cholangiocarcinoma (CCA) [154], upper aerodigestive tract cancer (UADT, [155]), nasopharyngeal carcinoma [156][157][158][159] and prostate cancer [160] but they rely on a small sample size which leads to a considerable lack of statistical power and ethnic and geographic differences that may account for the discrepancies observed. This polymorphism seems also to associate with myelodysplastic syndrome (MDS) and modulate acute myeloid leukemia (AML) transformation in MDS patients influencing survival of MDS and AML patients [161]. [162].…”
Section: Variants Of Ogg1 (Rs2072668 and Ser326cys) In Combination Wmentioning
confidence: 99%
“…Two PSC patients with CCA were found to be heterozygotic for NEIL1 Gly83Asp SNP [200], however the small number of individuals analysed does not allow drawing any conclusion on the association with CCA. The NEIL1 rs4462560 SNP was reported to be associated with MDS [161].…”
Section: Variants Of Ogg1 (Rs2072668 and Ser326cys) In Combination Wmentioning
confidence: 99%